Breather Stability in One Dimensional Lattices with a Symmetric Morse Potential - Cortez, H.; Drigo Filho, E.; Ruggiero, J.R. (Trends in Computational and Applied Mathematics, 2008)
Harmonic one dimensional lattice with an additional Morse potential on site has been used to describe DNA macromolecules properties. We analyze a modification of this lattice introducing a symmetric Morse potential. The existence and stability of the breather is studied in this modified system. We obtain harmonic bifurcation and determine the effective mass of the mobile breather.